FAKTOR-FAKTOR PENENTU NIAT BERKUNJUNG ULANG STUDI PADA TURIS DI TAMAN SARI YOGYAKARTA - Puana Putri Maharani; Usep Suhud; Dewi Agustin Pratama Sari (Yayasan Education and Social Center, 2023)
The purpose of writing this research is to examine the effect of electronic word of mouth (e-WOM) on perceived value, destination image, and destination trust. Then the influence of perceived value, destination image, and destination trust on revisit intention for Taman Sari Yogyakarta tourists. The data collection method uses a survey, with instruments in the form of questionnaires distributed online. Respondents in this study were aged 17-45 years, domiciled in DKI Jakarta and Yogyakarta. As many as 227 respondents were involved, data were analyzed using SPSS version 25 and SEM (Structural Equation Modeling) with AMOS software version 24. The results of this study indicate that e-WOM has a positive and significant effect on perceived value, e-WOM has a positive and significant effect on destination image, e-WOM has a positive and significant effect on destination trust, perceived value has a positive and significant effect on revisit intention, destination image has a positive and significant effect on revisit intention, and destination trust has no effect on revisit intention